Rising Tempers, Rising Temperatures : A Look at Climate Change, Migration and Conflict and the Implications for Youth in the Sahel Region - Alda, Erik (World Bank, Washington, DC, 2016)
Section one of the papers provides a brief overview of the relationship between the Sahel region of Africa and climate variability trends and predictions, ultimately posing the primary research question of the study: Is the Sahel region more likely to have a higher probability of conflict and migration as a result of climate change and climate change-related events? In section two, research and analysis aim to identify causal paths between climate change, migration, and conflict via structural equation modeling focusing on recent climate change trends in the Africa and Sahel regions, particularly changes in temperature and rainfall, and analyzing the consequences of this climate variabil¬ity, namely migration and conflict. Section three brings the aspect of youth into the analysis, arguing that youth living in the rural Sahel region will likely find themselves particularly vulnerable to in¬creased climate change and variability, which will have direct and indirect implications on the security and livelihoods of these individuals. The paper explores the past, current and predicted issues faced by rural Sahel youth affected by the impacts of climate change, such as chronic unemployment and engagement in the illicit sector due to rural to urban migration from regions affected by drought, desertification and resource scarcity. The final section of the paper offers policy recommen¬dations for addressing negative climate-change related consequences through two key paths of intervention: (i) climate change adaptation measures and (ii) conflict and crime prevention measures.